PENGARUH KUALITAS DAN HARGA TERHADAP KEPUASAN PELANGGAN DAN MINAT EWOM SAYURAN ORGANIK DI WARUNG SEHAT 1000 KEBUN - Velanda Ahtayary Putri; Agriani Hermita Sadeli; Pandi Pardian; Trisna Insan Noor (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Organic vegetables are one of the organic food products that are widely consumed by the public, including the customers of Warung Sehat 1000 Kebun. However, the view that the quality and price of organic vegetables is no better and cheaper than non-organic vegetables makes researchers want to know whether it affects customer satisfaction and whether there is an interest of customers to do e-word of mouth (social media) or the wide-ranging internet. This study aims to describe Warung Sehat 1000 Kebun's consumer behavior regarding product quality and prices, to customer satisfaction, and e-word of mouth (eWOM) interest. The method used in this study is an explanatory method to test hypotheses with Partial Least Square (PLS) analysis tools. The results showed that satisfaction was significantly influenced by the quality and price of the product. While e-wom's interest is not significantly influenced by both product quality, product prices, and customer satisfaction.